Changing Landscape of Head and Neck Squamous Cell Carcinoma and Nasopharyngeal Carcinoma Treatment and Survival Trends in Thailand: A 13-Year Multicenter Retrospective Study of Patients - Nuttapong Ngamphaiboon; Arunee Dechaphunkul; Chanida Vinayanuwattikun; Pongwut Danchaivijitr; Thanaporn Thamrongjirapat; Anussara Prayongrat; Tanadech Dechaphunkul; Rungarun Jiratrachu; Poompis Pattaranutaporn; Chuleeporn Jiarpinitnun; Jiraporn Setakornnukul (JCO Global Oncology)
PURPOSEThe incidence and survival rates of head and neck squamous cell carcinoma (HNSCC) and nasopharyngeal carcinoma (NPC) vary globally, influenced by factors such as ethnicity, lifestyle, and health care systems.METHODSA retrospective analysis was conducted on patients with HNSCC treated between 2008 and 2020 in four major Thai academic cancer centers, using a multidisciplinary multicenter database. The study focused on the evolution of patient characteristics, survival changes, and treatment landscape alterations over time.RESULTSAmong 6,319 patients, the most common primary sites were nasopharynx (33%), oral cavity (23%), oropharynx (17%), larynx (15%), and hypopharynx (8%). An increase in human papillomavirus–related oropharyngeal carcinoma was noted, from 13% in 2008 to 42% in 2019-2020. The majority of patients presented with locally advanced (LA) stages (IVa/b: 50%, III: 26%). Chemoradiotherapy (54%) and surgery (24%) were the main treatments, with cisplatin (79%) being most commonly used in chemoradiation. Overall survival (OS) improved annually across all subsites, correlating with an increase in intensity-modulated radiotherapy (IMRT) use, from 25% in 2008 to 90% in 2019-2020. The median follow-up duration was 4.59 years, with a minimum of 2.75 years. Patients treated with IMRT had significantly longer OS compared with those treated with non-IMRT techniques, in both NPC and non-NPC HNSCC (P < .001).CONCLUSIONTo our knowledge, this is the largest study in Thailand that demonstrates increasing survival outcomes in patients with HNSCC and NPC, despite commonly presenting with LA stages. The increasing use of IMRT may be contributing to improved survival outcomes in both patients with NPC and non-NPC HNSCC patients.